Odpowiedzi

Najlepsza Odpowiedź!
2010-03-12T16:27:08+01:00
4(x+7)(x+6)-(2x+3)Do potęgi 2 +1=0
4(x²+6x+7x+42)-(4x²+12x+9)+1=0
4x²+52x+168-4x²-12x-9+1=0
40x=-160
x=-4


b)
x √2 + 3 < 2x + 5

x √2 - 2x<-3 + 5

x(√2-2)<2/:(√2-2)


x>2/(√2-2)
1 5 1
2010-03-12T16:32:13+01:00
4(x+7)(x+6)-(2x+3)² +1=0
4(x²+6x+7x+42)-(4x²+12x+9)+1=0
4x²+24x+28x+168-4x²-12x-9+1=0
40x = -84+9-1
40x=-160 /:40
x=-4




x√2 + 3 < 2x+5
-2x+x√2<5-3
x(√2-2) < 2 /:(√2-2)
x > 2 /(√2-2)
Zmieniony znak dlatego,że dzielone było przez liczbę ujemną,bo (√2-2) to wychodzi okolo 1,41 - 2=-0,59
1 5 1
  • Użytkownik Zadane
2010-03-12T16:40:38+01:00
Patrz zalcznik
jesli masz pytanie pisz na pw
1 5 1